Missouri Juvenile Court Records, 1994 ([Verlag nicht ermittelbar], 1997)
This data collection describes in quantitative terms the volume of juvenile cases disposed in 1994 by courts having jurisdiction over juvenile matters (delinquency, status offense, and dependency cases) in Missouri. Inaugurated in 1975 and mandated in 1980, the Missouri Division of Youth Services collects and disseminates delinquency statistics about each case disposed during the previous calendar year. The data include a record of each case processed formally with petition and informally without petition, and contain an individual record on each delinquency, status offense, dependency, and special proceeding case disposed.